The Effect Of Hemoglobin Variant On HbA1c Measurement - Güven, Berrak; Can, Murat; Eskici, Zeynep (Fırat University, 2011)
HbA1c test is used in diagnosis and monitoring of diabetes mellitus. In this case report, a patient was presented that had discordance between clinical status and HbA1c result. Further investigations showed asymptomatic hemoglobin variant was caused this discordance.

HbA1c testi diabetes mellitusun tanısı ve takibinde kullanılmaktadır. Bu olgu sunumunda, klinik ile uyumsuz HbA1c sonucuna sahip bir hasta sunulmuştur. İleri araştırmalar asemptomatik hemoglobin varyantının bu uyumsuzluğa neden olduğunu göstermiştir.
Hemoglobin Varyantının HbA1c Ölçümüne Etkisi